Quantitative Ethnobotany Approach on Local Food Plants in Banceuy Traditional Village, Subang Regency, West Java - Raihandhany, Reza; Purnomo, Purnomo (Media Konservasi, 2025)
The Sundanese people of West Java, Indonesia, are well known for consuming raw plants, which are part of their food culture and are called lalapan. West Java consists of several traditional villages, one of which is Banceuy Traditional Village, located in Subang Regency. Usually, discourse about food is inseparable from culture since every place has unique dishes and cultures. This study aims to conduct a quantitative analysis of the inventory of food plant data using quantitative ethnobotanical indices. The research method used semi-structured interviews with 32 informants that consisted of two key informants and field-guided observation accompanied by one of the key informants around the village to identify and collect the food plant specimens. A quantitative data analysis was carried out using ethnobotany indices, namely, the Index of Cultural Significance (ICS), Use Values Index (UV), and Relative Frequency Citation (RFC). Banceuy indigenous people utilized 160 local food plant species belonging to 55 families. Fabaceae, Cucurbitaceae, Solanaceae, and Zingiberaceae were the dominant food plant families. These plant species were utilized as sources of carbohydrates, fruits, vegetables, spices, seeds, and beverages. The most applied food consumption manner by Banceuy indigenous people consisted of fresh food consumed, sauté, and boiling. Arenga pinnata had the highest ICS value (116) due to its utilization as seasoning and involvement in traditional rituals. Manihot esculenta and Carica papaya had the highest value in UV (1.81 & 1.69) and RFC (0.97) as they were used for daily consumption.